Influence of prehospital airway management on neurological outcome in patients transferred to a heart attack centre following out‐of‐hospital cardiac arrest. (11th May 2018) - Edwards, Timothy; Williams, Julia; Cottee, Michaela
Abstract: Objective: To describe the association between prehospital airway management and neurological outcomes in patients transferred by the ambulance service directly to a heart attack centre (HAC) post‐return of spontaneous circulation (ROSC). Methods: A retrospective observational cohort study in which ambulance records were reviewed to determine prehospital airway management strategy and collect physiological and demographic data. HAC notes were obtained to determine in‐hospital management and quantify neurological outcome via the cerebral performance category (CPC) scale. Statistical analyses were performed via χ 2 ‐test, Mann–Whitney U ‐test, odds ratios and binomial logistic regression. Results: Two hundred and twenty patients were included between August 2013 and August 2014, with complete outcome data obtained for 209. Median age of patients with complete outcome data was 67 years and 71.3% were male ( n = 149). Airway management was provided using a supraglottic airway (SGA) in 72.7% of cases ( n = 152) with the remainder undergoing endotracheal intubation (ETI). There was no significant difference in the proportion of patients who had a good neurological outcome (CPC 1 and 2) at discharge between the SGA and ETI groups ( P = 0.29). Binomial logistic regression incorporating factors known to influence outcome demonstrated no significant difference in neurological outcomes between the SGA and ETI groups (adjusted OR 0.73, 95% CI 0.34–1.56). Conclusion: In this observational study, there was no significant difference in the proportion of good neurological outcomes in patients managed with SGA versus ETI during cardiac arrest and in the post‐ROSC transfer phase. Further research is required to provide more definitive evidence in relation to the optimal airway management strategy in out‐of‐hospital cardiac arrest.